Competitive state anxiety for badminton athletes - Mantis, K.; Mavridis, T.; Antoniou, P. (2001)
The precompetition state anxiety for badminton athletes, was tested using the Competitive State Anxiety Inventory - 2. The CSAI-2 is a sport specific, self report inventory containing three subscales: somatic anxiety, cognitive anxiety and self-confidence. We recruited young badminton athletes who participated at the All Greek Men`s and Women`s Championship 1999. We tested 68 badminton athletes (39 male and 29 female) half an hour before the singles match. All athletes had at least two years experience at participating in badminton tournaments and were amateurs. The questionnaire (CSAI-2; Martens, Burton, Vealey, Bump & Smith, 1990) was translated and adapted into Greek by Kakkos and Zervas, 1993. The results indicated that the interference and existence of precompetition state anxiety was significant in the female badminton athletes (p< 0.01). Further, females had greater somatic anxiety and less self-confidence than males (p< 0.001). No significant differences were found for the cognitive subscale between men and women. The necessity to further research with other badminton samples of different age and level was emphasised.